Systemic Lupus Erythematosus and Pregnancy: A Single-Center Observational Study of 69 Pregnancies - Naseri, Estephania Pignaton; Surita, Fernanda Garanhani; Borovac-Pinheiro, Anderson; Santos, Marília; Appenzeller, Simone; Costallat, Lilian Tereza Lavras (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To evaluate the effects of pregnancy in systemic lupus erythematosus (SLE) patients.Methods The present article is a retrospective cohort study. Data were collected from medical records of pregnant women with SLE from January 2002 to December 2012 at Universidade Estadual de Campinas, in the city of Campinas, state of São Paulo, Brazil. Systemic lupus erythematosus and disease activity were defined according to the American College of Rheumatology and the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) criteria respectively. The means, standard deviations (SDs), percentages and correlations were performed using the SAS software, version 9.4 (SAS Institute Inc., Cary, NC, US).Results We obtained data from 69 pregnancies in 58 women. During pregnancy, a new flare was observed in 39.2% (n = 27). The manifestations were most common in patients with prior kidney disease, and mainly occurred during the third quarter and the puerperium. Renal activity occurred in 24.6% (n = 17), and serious activity, in 16% (n = 11). Of all deliveries, 75% (n = 48) were by cesarean section. Two maternal deaths occurred (3%). Preterm birth was the main complication in the newborns. The abortion rate was 8.7%. Severe SLEDAI during pregnancy was associated with prematurity (100%) and perinatal death (54%).Conclusion The maternal-fetal outcome is worse in SLE when the women experience a flare during pregnancy. The best maternal-fetal outcomes occur when the disease is in remission for at least 6 months before the pregnancy.
Keywords: systemic lupus erythematosus; pregnancy; obstetric complications; perinatal death